Microcredit as a public health initiative? Exploring mechanisms and pathways to health and wellbeing. (February 2021) - Ibrahim, Fatma; McHugh, Neil; Biosca, Olga; Baker, Rachel; Laxton, Tim; Donaldson, Cam
Abstract: The widening health gap between the best and worst-off in the UK requires innovative solutions that act upon the social, economic and environmental causes of ill-health. Initiatives such as microcredit have been conceptualised as having the potential to act on the social determinants of health. However, pathways that lead to this impact have yet to be empirically explored. People living on low incomes, who are financially-excluded, require access to credit to cope with everyday financial needs. While research shows the connections between debt and health, this link is often focused on over-indebtedness and negative health outcomes. In this paper, we investigate the impact of responsibly-delivered credit on the health and wellbeing of borrowers. In 2016-17, in-depth, semi-structured interviews were undertaken with fourteen borrowers from two microcredit providers offering personal and business microloans, operating in Glasgow, United Kingdom. Findings are presented, using social determinants of health as an analytic lens, and illustrated in a conceptual model explaining the loan mechanisms and pathways connecting microcredit to health and wellbeing. Microcredit, and the mechanisms through which it is delivered, were perceived by participants as positively impacting on their health and wellbeing. Access to flexible, responsibly-delivered, microloans enabled participants to plan and feel secure when faced with (un)expected financial events, reducing the associated stress, sustaining social relationships and empowering borrowers to take greater control over their lives. For some, receiving microcredit was stressful, as it is still a debt that needs to be repaid. Such stress can also be exacerbated by particular aspects of the lending model; for example, group lending. Our results contribute to growing evidence on the impact of financial inclusion approaches on health and wellbeing, highlighting the potential role of microcredit as a public health initiative and the need to support 'alternative' economic spaces in the UK to serve the financially-excluded. Highlights: Responsibly delivered credit can positively impact borrowers' health and wellbeing. Some aspects of group lending could negatively affect borrowers' wellbeing. Microcredit has the potential to act as a public health initiative. There is a need to invest in alternative economic spaces in the UK.